The Role of Strategic Agility in Enhancing Operational Performance in the Saudi Ministry of Health: The Moderating Role of Future Challenges - Abu Joma, Mahmoud Hussein; Al-Ruwaili, Abdul-Ilah Manahi (International Review of Management and Marketing, 2026)
The study aimed to examine the impact of strategic agility and its dimensions (environmental agility, technological agility, interactive agility, and marketing agility) on enhancing operational performance and its dimensions (quality, cost, flexibility, and delivery) in Saudi Ministry of Health. The study also sought to explore the moderating role of future challenges in the relationship between strategic agility and enhanced operational performance. The study employed a quantitative descriptive-analytical approach. SPSS was used to perform descriptive analysis of the study variables, including frequencies, percentages, means, and standard deviations. Smart PLS 4 was used for structural equation modeling, data analysis, results extraction, and hypothesis testing. The study population included all middle- and senior-level employees working in the Ministry of Health in Jeddah, totaling 2,837 employees. A stratified random sampling method was used to select a sample of 323 employees. The results indicated a statistically significant relationship between strategic agility and enhanced operational performance, with future challenges not moderating this relationship. The study recommended intensifying training programs and workshops aimed at enhancing employee participation in environmental agility initiatives, which would raise adherence to sustainable health standards and practices. It also recommended conducting future research to explore the impact of strategic agility on additional operational performance indicators, such as service innovation, decision-making quality, and responsiveness, to further understand the role of strategic agility in improving efficiency and effectiveness in healthcare operations.